PENGARUH STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL DAN GOOD GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA LHOKSEUMAWE - Mulia Andirfa; Muhammad Zubir (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2019)
In an organization, especially government organizations related to efforts to achieve the stated goals, can not be separated from the existence of elements of human resources as the driving force of the organization. Human resources determine whether or not walking, in addition to the availability of facilities and infrastructure. Organizations need quality human resources to be able to achieve their intended goals. So that there are qualified human beings or human beings who are effective and successful, need to sharpen human resources. Good governance is a form of success in carrying out the task of building the country in accordance with the planned goals. To achieve this goal every government must be able to manage the resources that exist in the country, one of the most important of which is finance. Government Accounting Standards (SAP) are accounting principles applied in preparing and presenting government financial reports so that Government Accounting Standards is a requirement that has the power law in an effort to improve the quality of government financial reports in Indonesia. This is supported by a statement in Law Number 32 of 2004 article 184 paragraph (3) concerning Regional Government stating: "The financial statements of the Regional Government are prepared and presented in accordance with Government Accounting Standards stipulated by Regional Regulations." With reference to Standards Accrual-based Government Accounting, it is expected that the financial statements produced will be comparable and useful for evaluating government performance. Then it can be stated that the application of accrual-based SAP will improve the quality of financial statements. Data analysis used in this study through multiple linear regression.